Myocardial infarction, ischaemic stroke and pulmonary embolism before and after breast cancer hospitalisation - Herk-Sukel, Myrthe P. P. van; Shantakumar, Sumitra; Kamphuisen, Pieter W.; Beest, Fernie J. A. Penning-van; Herings, Ron M. C. (Thrombosis and Haemostasis, 2011)
We studied the occurrence of myocardial infarction (MI), ischaemic stroke (IS) and pulmonary embolism (PE) before and after breast cancer hospitalisation compared with cancer-free controls. For this, women with a first breast cancer hospitalisation during 2000–2007 were selected from the PHARMO Record Linkage System, including drug use and hospitalisations of three million inhabitants in the Netherlands, and matched 1:10 by age to cancer-free women. The occurrence of MI, IS and PE were assessed in the 12 months before and after breast cancer hospitalisation. The study included 11,473 breast cancer patients, with a mean (± SD) age of 59 (± 14) years. Breast cancer patients were two to three times as likely as their cancer-free controls to have had a hospitalisation for PE, MI or IS in the 12 months before diagnosis, though prevalence was <1% in all groups. Breast cancer patients experienced an extreme high risk of PE in the first six months after diag- nosis (hazard ratio [HR] 23.5, 95% confidence interval [CI] 11.1–49.7 compared to controls), which declined gradually to a four times increased risk (HR 3.6, 95%CI 2.4–5.5) more than 12 months after breast cancer hospitalisation. However, incidence was low: less than five events per 1,000 person years during all time periods. For MI and IS we did not observe significant increased HRs after breast cancer hospitalisation compared to controls. Breast cancer patients seem to have a higher risk profile to develop MI and IS, and receive treatment that increases the risk of PE compared to cancer-free controls, although the frequency of hospitalisations was low.
Keywords: Breast cancer; incidence; ischaemic stroke; myocardial infarction; pulmonary embolism; risk factors